Reconstructing the Cooperative Rule of Law as an Alternative for Economic Empowerment of Rural Communities in Indonesia - Siregar, Sindi Safira Hanum; Riyanti, Indah; Suasungnern, Sineenat (International Journal of Contemporary Sciences (IJCS), 2024)
Cooperatives in the Indonesian economic system function as one of the efforts to achieve national development goals, namely creating a just and prosperous society in accordance with the principles of Pancasila and the 1945 Constitution. The legal basis of cooperatives in Indonesia is regulated by Law Number 25 of 1992 concerning Cooperatives. The purpose of this research is to study the development of cooperative law in Indonesia as an alternative to economic empowerment of rural communities, and analyse the legal construction of cooperatives as an alternative to economic empowerment of rural communities in Indonesia. This research is a normative legal research with a legislative approach and conceptual approach. The results show that the weaknesses in Law No. 25/1992 on Cooperatives, such as the unclear definition of cooperatives, unfulfilled principles, and lack of strict sanctions, indicate that the regulation needs to be reconstructed to address the existing problems and increase public trust in cooperatives. Thus, the reconstruction of Law Number 25 of 1992 on Cooperatives will not only improve cooperative governance, but also make a significant contribution to the economic empowerment of communities in Indonesia, especially in rural areas.